PENGARUH PERPUTARAN KAS DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PT. ASTRA INTERNASIONAL TBK PERIODE 2011-2020 - Tri Damayanti; Dewi Pangi Layla Azhari; Muhamad Syahwildan (Asosiasi Dosen Muda Indonesia, 2022)
The purpose of this study was to determine the effect of cash turnover and inventory turnover on the profitability of PT. Astra International Tbk. This research is a descriptive research with a quantitative approach. The data used is secondary data taken by the documentation method through the website www.astra.co.id. The method used is the classical assumption test, multiple regression analysis, t test, f test, and the coefficient of determination test using SPSS version 26.0. Based on the research, it shows that cash turnover and inventory turnover simultaneously have a significant and significant effect on profitability with a significance value of 0.000. While partially, cash turnover has a positive and significant effect on profitability with a significance value of 0.001. And inventory turnover has no positive and significant effect on profitability with a significance of 0.379.